2011
DOI: 10.1097/rli.0b013e31820577df
|View full text |Cite
|
Sign up to set email alerts
|

Dose Response to Paclitaxel-Coated Balloon Catheters in the Porcine Coronary Overstretch and Stent Implantation Model

Abstract: In the animal model, 2 paclitaxel matrix formulations were similar in respect of uptake in the vessel wall, and effective already at a dose of 1 μg/mm2. Except thrombotic events for the intentionally excessive dose, paclitaxel-coated balloons were well tolerated in the animal model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 117 publications
(93 citation statements)
references
References 24 publications
7
81
1
1
Order By: Relevance
“…Drug wash off rates of non-crosslinked PVP coatings, of which use was simulated for comparison, were with 48% and 95% during immersion and simulated use, respectively (Figures 4 and 6), considerably higher. Interestingly, observed PTX wash off rates of photochemically crosslinked PVP-coatings are in the same range as above-mentioned PTX losses of 26%-42% reported in literature for balloons coated with urea or iopromide, respectively, during in vitro passage through a hemostatic valve and a guiding catheter [11,12]. Comparison to literature values should however be handled with care, as different in vitro models are involved.…”
Section: Simulated Use Of Pvp-coated Dcbsupporting
confidence: 72%
See 1 more Smart Citation
“…Drug wash off rates of non-crosslinked PVP coatings, of which use was simulated for comparison, were with 48% and 95% during immersion and simulated use, respectively (Figures 4 and 6), considerably higher. Interestingly, observed PTX wash off rates of photochemically crosslinked PVP-coatings are in the same range as above-mentioned PTX losses of 26%-42% reported in literature for balloons coated with urea or iopromide, respectively, during in vitro passage through a hemostatic valve and a guiding catheter [11,12]. Comparison to literature values should however be handled with care, as different in vitro models are involved.…”
Section: Simulated Use Of Pvp-coated Dcbsupporting
confidence: 72%
“…Therefore, drug wash off rates during transit of the device through the vascular system should not be underestimated. For instance, while Kelsch et al [11] reported percental PTX wash off rates of up to 26% and 36% for urea-or iopromide-based DCB, respectively, Berg et al [12] observed a drug wash off rates of 42% for an iopromide-based formulation, both during in vitro passage through a hemostatic valve and a guiding catheter.…”
Section: Introductionmentioning
confidence: 99%
“…All published pharmacokinetic data presented to date has been derived from computational models or experimental studies using normal vessels 11, 12, 13, 14. PCB showed a uniform drug distribution on a non‐stented vessel surface 15.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent drug-coated balloon catheters developed in Europe and the USA came closer to the original principle, which is to use 3 μg paclitaxel/mm² in conjunction with an additive to protect the drug from premature release while at the same time facilitating fast and complete release upon balloon inflation at the target site. Examples are DIOR™ II (EuroCor, Germany) with the film-forming agent shellac as an additive [36,57], In.Pact catheters for coronary and peripheral applications (Medtronic, USA) with urea as an additive [49,51,69], and Pantera™ Lux (Biotronic, Germany) with the amphiphilic butyryl-tri-hexyl citrate as an additive [70]. Several similar developments have been presented but no data published in scientific journals are available.…”
Section: üBersicht 351mentioning
confidence: 99%
“…The tolerance of local overdose, e. g., due to overlapping inflation of paclitaxel-coated balloons either without stents or combined with premounted bare metal stents, has been addressed in preclinical studies in coronary and peripheral arteries. Whereas the treatment of up to 9 or 10 μg/mm² vessel wall administered by a single or two overlapping high dose balloons (iopromide or urea -paclitaxel) was tolerated by porcine coronary arteries [42,49], the treatment of the same vessel segment with 3 high-dose overlapping balloons (urea-paclitaxel-coating) caused thrombotic occlusion of some arteries. Milewski et al [60] found that 2 overlapping balloons did not cause problems but were required to achieve the desired inhibition of neointimal proliferation in porcine peripheral arteries.…”
Section: üBersicht 351mentioning
confidence: 99%